Pengaruh Manajemen Waktu terhadap Hasil Belajar Peserta Didik Mata Pelajaran Fiqih Di Mts Al-As’ad Brambang Diwek Jombang - Moch. Sya’roni Hasan; Karomah Tanjung Sari (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2021)
In order to obtain maximum learning outcomes, students must have persistence in learning and be able to manage time in learning. Good time management (regulation) will produce something good too, such as learning outcomes that match expectations. This research is a descriptive correlational study using a quantitative approach. Using numerial or numeric data analysis. The data collection method is a questionnaire (questionnaire) and observation. The subjects of this study were all students with a population of 30 students. The data analysis used is simple linear regression analysis. This study aims to determine the effect of time management on student learning outcomes in the subject of fiqh at Madrasah Tsanawiyah Al-As'Ad Brambang Diwek Jombang. The results of this study indicate (1) the time management of students at Madrasah Tsanawiyah Al-As'Ad Brambang. Diwek Jombang was declared good with a percentage of 43.33%, (2) The learning outcomes of students in fiqh subjects at Madrasah Tsanawiyah Al-As'Ad Brambang Diwek Jombang were stated to be quite good with a percentage of 60%, (3) There was a significant influence between time management on The learning outcomes of students in the subject of fiqh at Madrasah Tsanawiyah Al-As'Ad Brambang Diwek Jombang with a value of 0.019 are smaller than the probability value of 0.05.